Development and Molecular Characterization of Low Phytate Basmati Rice Through Induced Mutagenesis, Hybridization, Backcross, and Marker Assisted Breeding - Qamar, Zia-ul-; Hameed, Amjad; Ashraf, Muhammad; Rizwan, Muhammad; Akhtar, Muhammad (Frontiers in Plant Science, 2019)
Breeding low phytate crops is the most viable solution to tackle mineral deficiencies. The objective of the present study was to develop high yielding, low phytate (lpa) basmati rice cultivars. Three homozygous lpa mutants, Lpa5, Lpa9 and Lpa59, were developed through induced mutations (gamma rays 60Co) and identified by colorimetric and High Performance Liquid Chromatography (HPLC) analysis. These mutants showed 54-63% reduction in phytic acid but had poor germination and yield. To improve these traits, hybridization and back cross breeding involving Lpa5, Lpa59 and parent cultivar Super basmati were performed and F2:3, F3:4, BC1F2:3 and BC1F3:4 generations were developed and screened to target the objective. Within the F2:3, homozygous (226), heterozygous (65) and wild type (46) lpa recombinants were identified. Within the homozygous lpa category, four recombinants (Lpa5, Lpa6, Lpa7 and Lpa30) showed improved germination. Within the F3:4 generation, 86 homozygous lpa recombinants were identified. Further selection, on the basis of better plant type and the low phytate trait resulted in the selection of 38 recombinants. Grain quality and cooking characteristics of these selected recombinants were comparable as compared to parent cultivar. Within the BC1F2:3 generations, two homozygous Lpa recombinant lines, Lpa141 and Lpa205, were selected out of 220. Screening of the BC1F3:4 generation for the desirable agronomic and low phytate trait also resulted in the selection of two homozygous lines. Finally, seven recombinants i.e. Lpa12-3, Lpa111-1, Lpa141, Lpa56-3, Lpa53-4, Lpa99-2 and Lpa205-4 out of 42 homozygous low phytate lines were selected on the basis of yield improvement (4-18%) as compared to parent cultivar. For molecular characterization of the Lpa trait, previously reported Lpa1-CAPS and Lpa1-InDel and functional molecular markers were applied. Results indicated the absence of the Z9B-Lpa allele and XS-Lpa mutation in the OsMRP5 gene in tested mutants, possibly suggesting that there may be new mutations or novel alleles in tested mutants that need to be identified and then fine mapped for subsequent utilization. To our knowledge, this is the first report of low phytic acid rice mutant development and their improved germination and yield through backcross breeding in basmati rice.